Perbandingan Indepedensi Lembaga Anti-Korupsi: Studi Komparatif antara Komisi Pemberantasan Korupsi (KPK) Indonesia dan Malaysian Anti-Corruption Commission (MACC) - Jessica Diva Anggraini; Vita Mahardhika (Universitas Muhammadiyah Sumatera Barat, 2026)
The Corruption Eradication Commission (KPK) of Indonesia and the Malaysian Anti-Corruption Commission (MACC) share the same primary objective—to combat corruption within their respective countries. However, the two institutions exhibit significant differences in terms of organizational structure, level of independence, and investigative mechanisms. This study aims to analyze how the degree of institutional independence influences the effectiveness of anti-corruption efforts in both countries and to provide insights into institutional practices that could serve as a reference for strengthening anti-corruption bodies in Indonesia. The research employs a normative juridical method with a comparative approach, analyzing criminal law regulations related to corruption offenses applicable in both countries, as well as comparing the implementation and institutional independence of their respective anti-corruption agencies. The findings indicate that, although Indonesia’s KPK possesses a higher degree of independence and broader authority than Malaysia’s MACC, the latter demonstrates greater strength in its multilayered external accountability mechanisms and its structured approach to prevention and public education.